Crossing borders as ‘new’ academics in contested times: Reflexive narratives of curriculum change and transformation - Rink, Bradley; Mohamed, Kharnita; Ngoasheng, Asanda; Behari-Leak, Kasturi (Critical Studies in Teaching and Learning, 2023)
This paper takes a reflexive and narrative approach to exploring three academics’ journeys of curriculum transformation at the height of the #Rhodesmustfall and #Feesmustfallmovement in South Africa. Their narratives tell the story of individual and shared border crossings which illustrate how ‘new’ academics transcend limitations and separations between people, knowledge andcurricula. Decoloniality in curricular and pedagogical change are explored through the lenses of the three academics and an academic developer supporting their journey. The narratives show that decolonial curricular and pedagogies are about good teaching and a greater understanding of students and their needs. Authors’ reflexive narratives aredeeply informed by the contextsin which they are implementing curriculum transformation. Thispaper is underpinned by the theoretical framework of Archer’s social realism, reflexive curricula,and border crossing. Reflecting on their curriculum transformation journeys, the authors come to realise that openness to learning is the key ingredient required for curriculum change to take place so that higher education can be accessible and relevant to the majority of students